A randomised, double-blind, placebo-controlled trial examining the dose-dependent effects of acute alcohol intoxication on neurocognitive performance - Blair Aitken; Brook Shiferaw; Luke A. Downey; Brooke Manning; Thomas Arkell; Michael G. Lenné; Jonny Kuo; Amie C. Hayley (Psychopharmacology, 2026)
Rationale Acute alcohol intoxication impairs cognitive and motor control, elevating risk in safety–critical contexts. While blood alcohol concentration (BAC) quantifies exposure, it does not reflect real-time functional impairment. Mobile, performance-based assessments may offer scalable detection tools, but their sensitivity under controlled alcohol challenge requires further validation. Objectives To evaluate the sensitivity of a mobile cognitive assessment (DRUID®) to alcohol-induced impairment across low and moderate intoxication levels and examined objective cognitive performance and subjective intoxication within a unified framework. Methods In a randomised, double-blind, placebo-controlled, within-subjects trial, 30 healthy adults (33% female; aged 23–49 years) completed neurocognitive testing following placebo, low-dose alcohol (mean peak BAC 0.04%), and moderate-dose alcohol (mean peak BAC 0.07%). Cognitive performance was measured using the Cambridge Neuropsychological Test Automated Battery (CANTAB) and DRUID®, while subjective effects were assessed via the Brief Biphasic Alcohol Effects Scale and a single-item intoxication rating. Results Moderate alcohol intoxication significantly impaired spatial working memory, sustained attention, and psychomotor control (all p < 0.05), and elevated DRUID® impairment scores at 130 min post-dose relative to placebo ( p < 0.001). Low-dose alcohol increased subjective intoxication and sedation (both p < 0.001) without measurable cognitive impairment. Conclusions Moderate alcohol produced persistent neurocognitive deficits despite dissociation between subjective and objective measures. Findings support performance-based impairment models and highlight mobile cognitive tools such as DRUID® as practical candidates for real-time functional assessment in applied safety settings. Trial registration ACTRN12623000528651, 19/05/2023.